Prevention of mother-to-child transmission of HIV in São Paulo State, Brazil: An update - Matida, Luiza Harunari; Da Silva, Mariliza Henrique; Tayra, Ângela; De Menezes Succi, Regina Celia; Gianna, Maria Clara; Gonçalves, Alexandre; De Carvalho, Heráclito Barbosa; Hearst, Norman (Wolters Kluwer, 2005)
Background: Sâo Paulo State has had the largest number of paediatric AIDS cases in Brazil. Since 1996, Sào Paulo (and Brazil nationally) has implemented an aggressive programme to reduce perinatal transmission. We have gathered available indicators to examine the programme's impact. Methods: We obtained data on reported AIDS cases from the AIDS surveillance system; data on the number of mother/infant pairs treated with zidovudine from the state logistics office responsible for distributing HIV medication; and the rates of perinatal transmission from a multicity study of the Brazilian Pediatric Society that includes a number of São Paulo facilities, which were compared with an independent study in 1995. The years for which data were available varied according to the source of the indicator. Results: Annual reported cases of AIDS as a result of perinatal transmission fell 58.9% from 1997 to 2002. The number of cases treated with zidovudine increased 73.7% from 1997 to 2004. The rate of perinatal transmission among babies born to HIV-positive mothers fell from 16% in 1995 to 2.4% in 2002 in the reference clinics that participated in the Brazilian Pediatric Society study. Conclusion: Both process and outcome indicators point to the effectiveness of efforts to reduce perinatal transmission in São Paulo State. © 2005 Lippincott Williams & Wilkins.
Keywords: AIDS; Brazil; HIV; Mother-to-child transmission; Perinatal transmission; Prevention